A spoiler recovery method for rapid diffusion measurements - Sørland, Geir Humborstad; Anthonsen, Henrik Walbye; Zick, Klaus; Sjöblom, Johan; Simon, Sébastien (Diffusion Fundamentals, 2011)
A method for rapid acquisition of multiple scans of NMR sequences is presented. The method initially applies two RF-pulses in combination with two magnetic field gradient pulses of opposite polarity, different strength and different duration. The basic idea is to spoil any magnetization in any direction before by letting the system recover to some degree of restoration of the thermal equilibrium magnetization. Thereafter any pulse sequence can be applied, and the next scan may be run immediately after the end of the pulse sequence. Thus one avoids the 5 times T1 delay between each scan. A set of PFG sequences are presented that apply the spoiler recovery method for significant reduction in acquisition time, and the method has been verified at 0.5 Tesla as well as at 11.7 Tesla.